(untitled) (Historia, 2021)
This work attempts to fill an important gap in the early history of missionary activity in South Africa. Unfortunately, it is only partly successful in doing so. I frequently found myself wishing that Schoeman had gone deeper and engaged many of the fascinating underlying issues which he skims over in attempting ..